Perubahan habitat manusia dan persekitaran serta implikasinya terhadap penyakit dan kesihatan serta pengurusannya - Jamaluddin Md. Jahi,; Muhammad Rizal Razman,; Azahan Awang, (Universiti Kebangsaan Malaysia, 2010)
Changes to human habitat and the environment especially in the context of urbanisation may lead to diseases which will inevitably affect human health. The existence of urban heat island, for example, during a stable atmosphere and temperature inversion traps atmospheric pollutants to remain near ground level and expose human beings to air pollution that can affect health and even death. The lithospheric environment which involves the utilisation of soil can also lead to changes especially through the use of artificial fertilisers. Changes to the hydrospheric environment may be traced through water pollution either through river, marine or domestic water supply systems. Water pollution is normally related to a number of water-borne diseases such as dysentry, typhoid and cholera. Changes involving the biospheric environment are normally related to the problem of pollution due to the use of toxic substances such as insecticides, pesticides and herbicides. However, one of the most obvious problems related to changes of human habitat and environment is dengue fever which is a vector-borne disease through aedes mosquitoes. This article deals with the physical environment, changes brought about by the development of human habitat and their implications on diseases and health. There are a number of legislation, regulations and non-legislative measures used to mitigate the problems of diseases and health used in this country to deal with changes to human habitat and the environment. This is also reviewed in this article